2019
DOI: 10.1155/2019/4328103
|View full text |Cite
|
Sign up to set email alerts
|

Model Test Study on the Antibreaking Technology of Reducing Dislocation Layer for Subway Interval Tunnel of the Stick‐Slip Fracture

Abstract: Based on the background of the Line F2-3 interval tunnel section of Jiujiawan in Urumqi Subway Line 1, this paper carries out the model test research on the antibreaking technology of the reducing dislocation layer in the tunnel section of the stick-slip fracture. The antibreaking effect of different locations and number of reducing dislocation layers in tunnel engineering is analyzed in this paper. The results show that when the double reducing dislocation layer, respectively, set between the surrounding rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…the vault displacement values in hard rock section are similar, but the vault displacement values of each monitoring section in soft rock section near interface increase obviously; that is, there is a significant displacement difference at the interface of soft and hard rock. e authors believe that a large number of circular staggered platform cracks ( Figure 10) occurring in tunnel lining at interface of soft and hard rock in literatures [7][8][9] are related to the displacement difference at the interface between soft and hard rock. e explanation is as follows: the tunnel can be regarded as a cantilever beam buried in hard rock, and the free end is constrained by the stratum of soft rock section, so the displacement of root of cantilever beam (located in hard rock section) is small.…”
Section: Displacement Difference Of Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…the vault displacement values in hard rock section are similar, but the vault displacement values of each monitoring section in soft rock section near interface increase obviously; that is, there is a significant displacement difference at the interface of soft and hard rock. e authors believe that a large number of circular staggered platform cracks ( Figure 10) occurring in tunnel lining at interface of soft and hard rock in literatures [7][8][9] are related to the displacement difference at the interface between soft and hard rock. e explanation is as follows: the tunnel can be regarded as a cantilever beam buried in hard rock, and the free end is constrained by the stratum of soft rock section, so the displacement of root of cantilever beam (located in hard rock section) is small.…”
Section: Displacement Difference Of Interfacementioning
confidence: 99%
“…However, the survey of seismic damage after Wenchuan earthquake in China showed that the seismic damage of tunnel also mainly occurred in geological section at interface of soft and hard rock, and the tunnel linings were peeled, cracked, staggered, and collapsed in different degrees, such as the Baiyunding Tunnel from the G213 highway of Yingxiu to Dujiangyan in Sichuan Province and Longxi Tunnel on the Yingdu expressway. e tunnel linings of interface section between soft and hard rock on these two lines showed circumferential cracks with 1 cm∼3 cm widths after earthquake [2,[7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Through investigation, it is found that strong earthquake can induce the activation of the stick-slip fault, and the dislocation of the fault is the primary factor causing the serious damage of the tunnel across the stick-slip fault (Cui, G. Y., and Wang, X. L., 2019;(Baziar, M. H., et al, 2016;Ardeshiri-Lajimi, S., et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, more and more experts and scholars have done a lot of research on the anti-breaking measures and reducing dislocation measures. Relying on the tunnel project of Urumqi Metro Line 1 crossing the F2-3 section of Jiujiawan active fault, Cui, G. Y., et al (2019) adopted the method of model test to make a comparative analysis of the different anti-breaking effects of the reducing dislocation layer under different construction position. Shahidi, A. R., and Vafaeian, M. (2005) carried out a series of studies on the Koohrangs hydraulic tunnel in Greece, and compared and analyzed the in uence of the anti-breaking effect of the reducing dislocation joint with different spacing under the in uence of the stick-slip fault.…”
Section: Introductionmentioning
confidence: 99%
“…Strong earthquakes can induce the activation of stick-slip faults [6]. e stick-slip dislocation of faults is the most important factor leading to serious damage of tunnel structures, and strong earthquake vibration is the second major factor.…”
Section: Introductionmentioning
confidence: 99%